2019
DOI: 10.21608/zumj.2019.14733.1344
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of primary postpartum hemorrhage at Zagazig University Hospitals

Abstract: Background: postpartum hemorrhage (PPH) is an obstetrical emergency that can occur after vaginal or cesarean delivery. It is the most common cause of maternal morbidity and may be complicated by shock, renal failure, acute respiratory distress syndrome, coagulopathy, and Sheehan syndrome. PPH is one of the top five causes of maternal death in both developed and developing countries. The Aim of work to assess the incidence and outcome of primary PPH in Zagazig University Hospitals to assess magnitude of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Any potential for improvement in management of these two disorders should be investigated (2) . Definition of PPH is the loss of 500 ml of blood in vaginal delivery or 1000 ml in Caesarean Section (CS) from the genital tract within 24 h of the delivery of the baby (3) . It is classified as: Minor PPH (blood loss 500-1000 ml) and major PPH (more than 1000 ml).…”
Section: Introductionmentioning
confidence: 99%
“…Any potential for improvement in management of these two disorders should be investigated (2) . Definition of PPH is the loss of 500 ml of blood in vaginal delivery or 1000 ml in Caesarean Section (CS) from the genital tract within 24 h of the delivery of the baby (3) . It is classified as: Minor PPH (blood loss 500-1000 ml) and major PPH (more than 1000 ml).…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the mean age of group I and group II were not statistically significant (Table 1). 13 observed at baseline, there was no significant difference between carbetocin and oxytocin in terms of mean age, where mean was 30 years and 31 years respectively. The higher mean age may be due to geographical variations, racial, ethnic differences, genetic causes, different lifestyle and increased life expectancy may have significant influence in their study patients 11 .…”
Section: Resultsmentioning
confidence: 65%
“…Safety of carbetocin following vaginal births and emergency Cesarean sections has not been established, though studies have suggested efficacy following vaginal births to that following Cesarean sections 11 . Some studies have shown that a 10 to 70 μg dose following vaginal delivery caused contractions and no adverse side effects 13 . The recommended dose for an average adult female is 100 μg, administered slowly over a minute 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Another study discovered a link between PPH occurrence and prior medical history, anemia, and previous PPH. 7 According to one study, women who had wound dehiscence after a cesarean section had a high rate of anemia, and as a result of the underlying anemia, they were more vulnerable to infection. 8 A case-control study looked at the risk factors for surgical site infection after cesarean section and discovered that only 2.4 percent of women got it.…”
Section: Discussionmentioning
confidence: 99%